Improving the Methodology of using General and Special Training Tools to Increase the Physical Fitness of Weightlifters (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study develops a new version of general and special training tools and methods to improve the physical fitness of weightlifters. In order to improve the fitness of athletes, general training exercises are used to increase physical qualities such as strength, endurance, speed and flexibility and to work on them, to train them in the necessary skills for competition techniques and physical exercises. According to the nature and direction of the effects of the tools used, physical training is divided into general physical training (GPT) and special physical training (SPPT). The aim of developing this methodology is to improve the results of weightlifters in sports competitions in two wrestling events.